Macular Hole after Laser In Situ Keratomileusis in a 26-Year-Old Patient - Guzel Bikbova; Toshiyuki Oshitari; Madoka Sakurai; Takayuki Baba; Shuichi Yamamoto (Case Reports in Ophthalmological Medicine)
The purpose of this study is to describe the 26-year-old patient with developed macular hole after bilateral laser in situ keratomileusis (LASIK). A macular hole with sharp margins and irregular surface of surrounding retina appeared in the left eye of the female 26-year-old patient two months after LASIK for correction of myopia (followup of 6 months). Although the best corrected visual acuity (BCVA) after LASIK was 1.0, after the macular hole has developed BCVA became 0.5. After surgery, the final visual acuity recovered to 0.7. Macular hole may develop after LASIK for myopia correction due to unknown changes of vitreoretinal interface. Complete informed consent must be obtained from patients with high myopic eyes before LASIK.